Community Knowledge and Compliance in Doing Prevention of COVID-19 - Setyawati, Dewi; Ningrum, Mei Yolla (South East Asia Nursing Research, 2021)
Community compliance in taking measures to prevent transmission of COVID-19 must be based on good knowledge about COVID-19 so that it can break the chain of transmission of COVID-19. The objective of this research to determine the relationship between the level of community knowledge about COVID-19 with compliance to prevent COVID-19 at the Community Health Center of Jati Kudus. This study used a quantitative analysis with a cross-sectional approach. The population was 115 people treated at Community Health Center of Jati Kudus with range aged 17-35 years, then got 89 respondents were obtained using the purposive sampling technique. The instrument used was a questionnaire. From the results of univariate data testing, 65 respondents (73%) had good knowledge of COVID-19, while those who had sufficient knowledge were 24 people (27%). The results showed that all respondents complied with the prevention measures for COVID-19 with a percentage of 100%. Based on the bivariate test result, it was found that there was a relationship between the level of knowledge and compliance in preventing transmission of COVID-19 with a p-value of 0.034 and r (correlation coefficient) of 0.225. It can be concluded that there was a relationship between the level of public knowledge about COVID-19 and compliance with COVID-19 prevention at the Pubic Health Center of Jati Kudus.